Development of Digital Circuits Learning Media Using Articulate Storyline with the 4D Model - M. Zikrul Ansori; Delsina Faiza; Thamrin; Efrizon (Sagamedia Teknologi Nusantara, 2024)
Education plays a vital role in developing students' potential. With the advancement of Information and Communication Technology (ICT), innovations in education have evolved, particularly in creating more effective, inspiring, and motivating media, methods, and learning strategies. This research aims to develop a learning media using Articulate Storyline for the